The impact of migration on Vietnam household living standards - Ngoc Hung Pham; Tran Manh Dung; Anh Duc Le; Thuy Linh Le (Journal of Risk and Financial Management, 2022)
This study is conducted to investigate the impact of migration on living standards of households with migrants in the context of Vietnam. Data were collected from the results of Vietnam Household Living Standards in the time series. Blinder-Oaxaca decomposition was employed to decompose the source of differences in income between households with migrants and households without migrants. The results show that households with migrants in the multiyear dataset had a higher income than nonmigrant households, and migration had different impacts on expenditure at different quantiles. By conducting quantile regression, migration had positive impacts on expenditures at the 10% and 50% quantile, but no impact at the 90% quantile. Based on the findings, some implications in policies for managers, such as appropriate policies for poor workers in order to improve their living standards, especially poor households in rural or mountainous areas, are proposed.
Keywords: 650; Blinder-Oaxaca decomposition; household living standards; quantile regression migration; Vietnam